تأثير المستخلص المائي لأزهار الكركديه في مستوى أنزيمتي الكبدAST و ALT في مصل دم الأرانب المحلية - دباغ, مروان; علي, اكتمال (Latakia University Journal -Biological Sciences Series, 2016)
هدفت الدراسة الحالية إلى معرفة تأثير المستخلص المائي لأزهار الكركديه في مستوى أنزيمتي الكبد: الألانين ترانس أمينازAlanine Transaminase(ALT) والأسبارتات ترانس أمينازAspartate Transaminase (AST) في مصل دم الأرانب المحلية . استخدم في هذه الدراسة (12) أرنباً قسمت إلى مجموعتين (6) شاهدة و (6) تجريبية حيث جرعت المجموعة التجريبية بالمستخلص المائي فموياً , وبجرعة يومية قدرها150ملغ/كغ لمدة 28 يوماً (4 أسابيع) في حين جرعت المجموعة الشاهدة بالماء المقطر فقط ، بعد ذلك تم سحب الدم لإجراء القياسات البيوكيميائية كل 48 ساعة.أظهرت نتائج الدراسة انخفاضاً معنوياً ( (p<0.05في مستويات أنزيمتي الكبد AST و ALT في المجموعة التجريبية، على العكس من ذلك لم تظهر في المجموعة الشاهدة أية فروق معنوية بين مستويات الأنزيمتين خلال أسابيع التجريع.The present study aimed to investigate the effect of calyx aqueous extract of Hibiscus sabdariffa on liver enzymes Alanine and Aspartate Transaminases (ALT and AST)level.(12) Rabbits were used and divided into two groups : (6) the experimental group and (6) control group ,the control group became distilled water , while the experimental group received aqueous extract, that was administrated orally in adose of150 mg / kg body weight (b.w.) daily for28 days .Then blood was collected each 48 hours , the serum samples were taken and prepared to the biochemical tests to determine Alanine and Aspartate Transaminases (ALT and AST)level. The results showed a significant decrease (p<0.05) in ALT and AST levels in experimental group. In contrast, control group, have showed no significant differences in enzyme levels between weeks of administration.